Genetic drift drives rapid speciation of an Arctic insular endemic shrew ( Sorex pribilofensis ) - Ben J. Wiens; Fraser J. Combe; Bobette Dickerson; Lauren M. Divine; Veronica M. Padula; George K. Sage; Sandra L. Talbot; Andrew G. Hope (Molecular Ecology, 2022)
Episodes of Quaternary environmental change shaped the genomes of extant species, influencing their response to contemporary environments, which are changing rapidly. Island endemics are among the most vulnerable to such change, accounting for a disproportionate number of recent extinctions. To prevent extinctions and conserve island biodiversity it is vital to combine knowledge of species' ecologies with their complex evolutionary histories. The Bering Sea has a history of cyclical island isolation and reconnection, coupled with modern rates of climate change that exceed global averages. The endangered Pribilof Island shrew ( Sorex pribilofensis ) is endemic to St. Paul Island, Alaska, which was isolated from mainland Beringia ~14,000 years ago by rising sea levels. Using ~11,000 single nucleotide polymorphisms, 17 microsatellites and mitochondrial sequence data, we test predictions about the evolutionary processes driving shrew speciation across Beringia. Our data show considerable differentiation of S. pribilofensis from mainland sibling species, relative to levels of divergence between mainland shrews. We also find a genome‐wide loss of diversity and extremely low N e for S. pribilofensis. We then show that intraspecific genetic diversity is significantly related to interspecific divergence, and that differentiation between S. pribilofensis and other Beringian shrews is highest across loci that are fixed in S. pribilofensis , indicating that strong drift has driven differentiation of this island species. Our findings show that drift as a consequence of Arctic climate cycling can rapidly reshape insular biodiversity. Arctic island species that lack genomic diversity and have evolved in response to past climate may have limited ability to respond to modern environmental changes.